HARMONISING RESTORATIVE JUSTICE IN THE INDONESIAN LEGAL SYSTEM: INTEGRATING PANCASILA VALUES AND HUMAN RIGHTS PROTECTION - Zentoni, Zentoni (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2025)
The harmonisation of the concept of restorative justice in Indonesia is a significant step towards developing a judicial system that prioritises recovery and reconciliation, rather than the traditional approach that emphasises punishment. With the increasing integration of restorative justice principles into legal regulations, such as Attorney General Regulation No. 15 of 2020, National Police Chief Regulation No. 8 of 2021, and the inclusion of this concept in the 2023 Criminal Code, Indonesia is making substantial progress towards a more humane and effective legal system. This study employs a doctrinal legal approach, analysing various regulations and their application within the Indonesian legal system. The findings demonstrate that the application of restorative justice in Indonesia is strongly rooted in the values of Pancasila and the 1945 Constitution, which highlight the principles of social justice, humanity, and respect for human rights. By involving perpetrators, victims, and the community in the conflict resolution process, restorative justice provides space for the restoration of social relationships damaged by criminal acts, strengthens social cohesion, and minimises the negative impacts of the retributive justice system. However, the primary challenge lies in ensuring that the application of these principles does not lead to imbalance or injustice, particularly in more serious cases. Therefore, harmonising constitutional values with the implementation of restorative justice must be undertaken with great care to preserve the integrity of the Indonesian legal system and ensure the protection of human rights, while achieving a more comprehensive and sustainable form of justice.